Pengaruh Inkonsistensi Switching Light-Dark Mode Antar Aplikasi Terhadap Mental Workload dan Kinerja Pengguna Smartphone - Layla Ayu Mustika Putri; Alfian Nurlifa; Andik Adi Suryanto (JURIKOM (Jurnal Riset Komputer), 2026)
Visual inconsistency in user interface contexts, such as visual theme changes during mode switching (from Light to Dark Mode), is often considered an optional aesthetic element; however, its impact on user cognitive load and performance has not been widely researched. This study aims to analyze the effect of mode switching on subjective cognitive load, task completion time efficiency, and user performance accuracy in an interface interaction context. The method used in this experiment was a Quasi-Experimental Design with a posttest-only control group type, involving 40 respondents divided into two groups: static theme condition and mode switching condition. Subjective cognitive load was measured using the NASA-TLX instrument, while objective performance was evaluated through Task Completion Time and Error Rate. The results of this study indicate that the treatment group experienced an increase in cognitive load, with an average WWL score of 55.23, compared to the control group at 42.50. The frustration dimension was the highest, at 28.0, indicating emotional pressure due to interface inconsistency. Objectively, the application of mode switching slowed down task completion time by 3.65 seconds and increased the error rate by up to two times. Statistical test results also showed differences in all research variables, with a p-value < 0.005 and an effect size value on cognitive load of 0.816 (Large Effect). These findings lead to the conclusion that visual stability is an important factor in interface design, necessary for maintaining navigation efficiency, increasing user comfort, and minimizing interaction errors.